Nutrional analysis of male mackerel gyoza (Rastrelliger kanaguarta) fortififed with Kappaphycus alvarezii Seaweed - Muskirah, Muskirah; Harianti, Harianti; Salam, Ayusal; Angreni, Husni; Khairiyah, Zul (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
Food is very important as a source of nutrient for the body every day. Currently, the trend of fast food is increasingly attracting people’s interest without considering the nutrional content in it. Gyoza is a fast food similar to dimsum that has a savory and taste in the from of jiozia. Modification of gyoza filling using male mackerel (Rastrelliger kanaguarta) and Kappaphycus alvrezii seaweed is made as an alternative to healthy fast food. This study aims to determine the characteristic of the chemical and sensory quality of male mackerel gyoza (Rastrelliger kanaguarta) fortifed with Kappaphycus alvarezii seaweed. This research method was carried out in March-June 2025 using the experimental laboratory method with three treatments and repetitions for chemical test. The addition of Kappaphycus alvarezii seaweed to the nutrition of male mackerel gyoza had a significant effect (p<0.005) based on the ANOVA test, highest protein content in sample A without seaweed 19.97%, the highest iodine content in sample C fortified with 20 grams of seaweed 20.06 µg/g, the highest fiber content sample C fortified with 20 grams of seaweed with a result of 9.55%.